Scope and limitations of minimal invasive surgery in practice of pediatric surgical oncology - Bhatnagar Sushmita; Sarin Yogesh (Indian Journal of Medical and Paediatric Oncology)
Management of Solid tumors in children needs a comprehensive multimodality protocol based treatment plan. Open surgical removal of the tumors occurring in any of the sites such as abdomen, thorax, chest wall, HFN (head, face, neck), brain and extremities, is the option which has been traditionally practiced even in the present era and in most of the centers. Nevertheless with the advances in science and technology and with ever increasing usage and expertise of laparoscopy in children, it′s application has extended to treatment of solid tumors in children. A review of the scope of such intervention as well as the limitations of minimal invasive surgery in this specialized field of pediatric surgery has been attempted in this article.